Synthesis of glucose oxidase-PEG aldehyde conjugates and improvement of enzymatic stability - Vardar, Gokay; Altikatoglu, Melda; Basaran, Yeliz; Isildak, Ibrahim (TAYLOR & FRANCIS LTD, 2018)
In this article, aldehyde derivative of poly(ethylene glycol) (PEG) was synthesized directly with sodium periodate agent. To obtain a conjugate which possesses better stability, PEG aldehyde was bonded to native enzyme with different molar ratios. The conjugation reaction turned out to be efficient and mild. Colorimetric method was applied to evaluate the enzymatic activity of native GOD and its derivatives by introducing another enzyme, horseradish peroxidase. The GOD-PEG aldehyde conjugate with polymeric chains exhibited reduced enzymatic activity towards the catalytical oxidation of glucose, but with significantly increased thermal stability and elongated lifetime. When GOD was modified with PEG aldehyde the enzymatic activity was decreased 40% at 30 degrees C. However, when incubated at 60 degrees C the GOD-PEG aldehyde conjugate still retained the enzyme bioactivity of 40% bioactivity left after 4h, whereas the native GOD lost almost all the activity in 4h. The polymer chain attached, the more reduction of the enzymatic activity resulted, however, the longer the lifetime and higher thermal stability of the enzyme obtained.
Keywords: Thermal stability; covalent conjugation; glucose oxidase; PEG aldehyde; activity; ASPERGILLUS-NIGER; COVALENT IMMOBILIZATION; DEXTRAN-ALDEHYDE; STABILIZATION; PURIFICATION; PH; PEGYLATION; POLYMER; CHROMATOGRAPHY; TEMPERATURE; Biotechnology & Applied Microbiology; Engineering; Materials Science